ANALISIS KEBIJAKAN PROGRAM KARTU INDONESIA PINTAR ( KIPK) DALAM MENDUKUNG PENCAPAIAN SDGS 4 DI UNIVERSITAS NEGERI SURABAYA - Ayunda Putri Athamevia; Ivena Callista Putri; Firre An Suprapto; Indah Prabawati (Universitas Bandar Lampung (UBL), 2026)
The Indonesia Smart Card for Higher Education (KIP-K) program is a government scholarship aimed at supporting academically capable students from economically disadvantaged families. This study evaluates the implementation of the KIP-K program at Universitas Negeri Surabaya (UNESA) using a descriptive qualitative method. The evaluation is based on six indicators from William N. Dunn: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The results indicate that the program has been implemented fairly well through verification and field survey processes. However, several challenges remain, including limited administrative resources, lack of information transparency, and delays in fund disbursement. Improvements in coordination and information systems are needed to ensure the program operates more effectively and accurately. Keywords: KIP-K program, policy evaluation, educational assistance